Модернізація системи освіти України як державна і педагогічна проблема - Михальченко, М. І. (НТУ "ХПІ", 2010)
Детально вивчено актуальність процесу модернизації освітнього сегменту в сучасному суспільстві. Автор розкриває шляхи модернизації системи вищої освіти України та проблеми, які перешкоджають здійсненню цього процесу.

Studied in detail the relevance of the process of modernization of the educational segment in the modern society. The author reveals ways to modernize the higher education system of Ukraine, and impediments to implementation of this process.
Modernization of education system of Ukraine as the state and pedagogical problems
Keywords: інформатизація освіти; інноваційна освіта; глобалізація освіти; безперервність освіти